ANALISIS PENGARUH PELAKSANAAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PENCAPAIAN MAQASHID SYARIAH DI PERBANKAN SYARIAH INDONESIA (TAHUN 2012-2015) - Rifaldi Majid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
As Islamic banks operates in accordance to the Islamic principles and system, they should run to achieve the ultimate objectives of Sharia (Maqashid Sharia). The disclosure of the Islamic banking performances could be measured by sharia maqashid index (SMI) which distinguishes them from the other banks. This study aims to determine the effect of good corporate governance (GCG) implementation on Maqashid Sharia perspective measured by Sharia Maqashid index for the Indonesia Islamic banks for the periode of 2012-2015. Eight Islamic banks are included as samples seleceted using a purposive sampling technique. This research is a quantitative descriptive study and employs a multiple regression analysis as a data analysis method. The analysis is performed to determine the effect of commisioner board size, Sharia supervisory board size, and the board of directors on the achievement of SMI. The results show the size of commisioner board has a positive effect on achievement of SMI. However other two variables which are the sharia supervisory board size and the board of directors does not affect the achievement of SMIKeywords: Board Of Commisioners, the Sharia Supervisory Board, Board of Directors, Sharia maqashid Index.